2009
DOI: 10.1897/08-545.1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and toxicological characterization of an unresolved complex mixture‐rich biodegraded crude oil

Abstract: Chemical and toxicological characterization of unresolved complex mixtures in the water-soluble fraction of an artificially weathered Norwegian Sea crude oil was determined by a combination of chemical analysis and toxicity testing in fish in vitro bioassays. The water-soluble fraction of the crude oil was separated into 14 increasingly polar fractions by preparative high-pressure liquid chromatography. The in vitro toxicity (7-ethoxyresorufin O-deethylase activity, estrogenicity, and metabolic inhibition) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 42 publications
2
76
0
Order By: Relevance
“…This is not because they are not there, but because of the amount of work that such a study would involve and because it is methodologically impossible to analyze and characterize all pollutants. Even for fossil fuel residues found in the environment, the chemical structure of some fractions remains largely uncharacterized (Rowland et al 2001;Donkin et al 2003;Melbye et al 2009). Furthermore, the list of chemicals present in the environment must be several orders of magnitude longer than those ever reported, since hundreds of thousands of organic chemicals have been used by humankind.…”
Section: The Organic Anthropogenic Chemosphere In Coastal Watersmentioning
confidence: 99%
“…This is not because they are not there, but because of the amount of work that such a study would involve and because it is methodologically impossible to analyze and characterize all pollutants. Even for fossil fuel residues found in the environment, the chemical structure of some fractions remains largely uncharacterized (Rowland et al 2001;Donkin et al 2003;Melbye et al 2009). Furthermore, the list of chemicals present in the environment must be several orders of magnitude longer than those ever reported, since hundreds of thousands of organic chemicals have been used by humankind.…”
Section: The Organic Anthropogenic Chemosphere In Coastal Watersmentioning
confidence: 99%
“…Most studies on crude oil spills have focused on polycyclic aromatic hydrocarbons (PAHs), and have shown that these contaminants caused detrimental effects on various aquatic organisms [2][3][4][5][6]. Conversely, other constituents in the oil matrix, which were commonly referred to as an unresolved complex mixture (UCM) were less studied [7][8][9][10]. The UCM was composed of weathered oils, which originated from natural and/or anthropogenic sources, and was first recognized as the "hump" in the quantification of petroleum-contaminated sediment samples using gas chromatography (GC) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, have showed that the UCM constituents in sediment not only accumulated in benthic organisms, but also caused sub-lethal effects to these organisms [7][8][9][10][11]15]. For example, UCM contributed to the overall toxic effects of oils to the marine amphipod Corophium volutator and its contribution was separate from the PAHs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Their main characteristic is higher polarity which, as a consequence, affords higher water solubility and bioavailability/toxicity. [62][63][64] Furthermore, this fraction can also contain transformation products generated through weathering, such as oxidated polycyclic compounds which can be present at even higher concentrations than the parent compounds. 65 These have been reported in marine environmental matrices at toxic levels 66,67 and can be persistent.…”
Section: -61mentioning
confidence: 99%